Analisis Asset dan Hutang terhadap Pertumbuhan Laba Pada Perusahaan Sektor Energi Yang Terdaftar Di Bursa Efek Indonesia - Zuraida, Zuraida Zuraida; Nurhasanah, Nurhasanah Nurhasanah; Jummaini, Jummaini Jummaini; Wahyuddin, Wahyuddin Wahyuddin (Department of Management Faculty of Economics and Business, UNIVERSITAS MALIKUSSALEH, 2024)
This study examines the influence of Asset and Debt (DAR) to Profitability Growth in energy sector companies listed on the Indonesian Stock Exchange. The sample collection method used purposive sampling and obtained 25 companies from 2017-2022. The analysis tool used is Panel Data. The results of the research show that the condition of company assets as measured by Total Assets has a negative significant effect on profit growth and the cash debt variable estimated with DAR has a positive relationship but does not significantly affect lab growth in Energy Sector companies listed on the Indonesian Stock Exchange. Keywords: Profit, Asset, DAR.